GAMBARAN QUALITY OF WORK LIFE PADA KARYAWAN MILENIAL DI PT. X - Ida Ayu Chandrika Sastrawan; Zamralita; Daniel Lie (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
The millennial generation has taken part as much as 25.87% of Indonesia's population, where this population is included in the productive age category which can be an opportunity to accelerate economic growth. Millennials themselves are a generation that grew up in the industrial era 4.0, where they are known as a generation that is confident, creative, connected to one another, and masters the use of information technology. Compared to generation X, which is a generation that is very adaptive and more focused on results, the millennial generation is a generation that has different characteristics and provisions from other generations. Quality of work life is an employee's perception of a comfortable and pleasant working environment in order to be able to meet employee needs and support employees to work and develop better. There were 45 participants in this study, with the criteria for participants being employees working at PT. X, employees born from 1982 - 2004; employees who have worked for at least one year in the company, and employees with at least high school education. The measuring instrument for this study uses the Walton Model QWL measurement tool, with the addition of two dimensions, namely supervisors, and job characteristics based on (Rostiana & Suyasa, 2014), with a total of 65 questions. The results of the normality test show that the research data is normally distributed, with a high level of quality of work life.